Visual dysfunction in patients with idiopathic rapid eye movement sleep behavior disorder. (14th September 2019) - Li, Yuan; Zhang, Hui; Mao, Wei; Liu, Xiaonan; Hao, Shuwen; Zhou, Yongtao; Ma, Jinghong; Gu, Zhuqin; Chan, Piu
Highlights: iRBD patients showed decreased color discrimination, with an exception of green color. Stereopsis in iRBD patients was worse than controls. Visual illusion or hallucination were more common in iRBD patients, correlated to decreased fine motor function. Visual dysfunctions were found to be associated with cognition in iRBD patients. Abstract: Objective: Visual dysfunction is a common feature in α-synucleiopathies but rarely assessed in patients with idiopathic rapid eye movement sleep behavior disorder (iRBD). The current study is set to investigate the comprehensive visual function in iRBD as compared to patients of Parkinson's disease (PD) with RBD. Methods: Eighty-three iRBD subjects diagnosed with polysomnograph (PSG), 52 early PD patients (Hoehn-Yahr stages<3) with RBD symptom prior to onset of motor symptoms and 79 healthy controls without RBD diagnosed based on RBD Questionnaire-Hong Kong (RBDQ-HK) were enrolled in this study. Visual function including color discrimination, stereopsis function, visual illusion (VI) or hallucination (VH) were assessed in addition to UPDRS, Purdue Pegboard test (PPT) and cognitive tests. Results: Abnormal color discrimination and stereopsis were presented significantly higher in both iRBD and PD patients as compared to controls and more severe in PD than in iRBD. Color discrimination was decreased in all four color in PD patients but not green color in iRBD subjects. Stereopsis test was abnormal in both iRBD and PD, but the proportion of subjects with abnormal stereopsis was significantly higher in PD patients (69.6% vs 42%). Similar number of subjects with iRBD and PD were presented with illusion but only PD patients reported more hallucination. Changes of visual function were associated with age and cognition in both iRBD and PD subjects but was also affected independently by disease duration and clinical stage or fine motor function in PD. In addition, decreased fine motor function demonstrated by PPT was also observed in some iRBD subjects. Conclusion: Our results demonstrated comprehensively that visual dysfunction was present in iRBD subjects similar but in a less degree of severity to PD patients, and associated with age, cognition and motor deficit. Whether or not it can be useful in predicting iRBD conversion to PD warrants further investigation.